Leveraging Social Media For Enhanced Profitability and Growth: Evidence From Small and Medium Scale Enterprises (SMEs) in Ghana - Padi, Abigail; Musah, Alhassan; Abekah Keelson, Solomon; Adjei , Linda (School of Business, IPB University (SB-IPB), 2024)
Background: Social media usage in Ghana is experiencing rapid growth. Leveraging social media can empower SMEs to overcome their challenges and enhance their visibility and profitability in the competitive business landscape.Purpose: This research investigated the utilization of social media tools in the marketing communication strategies of Small and Medium-scale Enterprises (SMEs) and explored their adoption. Additionally, the study examined the impact of social media usage on the profitability and growth of SMEs. Design/methodology/approach: The research aimed to survey 387 SMEs, with 200 providing fully completed questionnaires for analysis, resulting in a 52% response rate a notably reasonable figure compared to prior studies with smaller sample sizes.Findings/Result: The findings revealed that Facebook was the predominant social media platform employed by SMEs in Ghana, followed by Instagram, Twitter (X), TikTok, and LinkedIn. Notably, SMEs continued to heavily rely on their corporate websites for marketing communication. The study demonstrated a positive correlation between SMEs' use of social media and their profitability, indicating that social media usage enhances their financial performance. Furthermore, a positive and significant relationship was identified between SMEs' utilization of social media tools and their growth in Ghana. These results suggest that SMEs can leverage social media in their marketing communication efforts to drive sales and enhance overall growth prospects.Conclusion: The study indicated a positive association between social media usage and SMEs’ profitability, suggesting enhanced performance in terms of profits. Moreover, leveraging social media can drive sales and improve growth prospects. Overall, the study provides empirical evidence of the profound impact of social media tools on SMEs in Ghana which is consistent with the expectations of diffusion of innovation theory and technology acceptance theory.Originality/value (State of the art): The study contributes a notable gap by delving into the adoption and impact of social media on Small and Medium-sized Enterprises (SMEs) in both developing and developed countries. In addition, this study offers valuable insights for SMEs seeking to leverage social media for expansion, growth, and improved performance. Keywords: social media, SMEs, marketing communication, growth prospects, Ghana